Brazil’s Northern Arc Ports and the frozen beef export chain: bottlenecks and economic benefits - Scotton, Bruna; Silva, Nathan Gomes da; Rocha, Fernando Vinícius da; Caixeta Filho, José Vicente (Revista de Administração da UFSM, 2020)
Consumer demand for consistently high quality meats has exposed a series of problems in the Brazilian frozen beef agro-industrial logistics chain arising from a lack of adequate infrastructure to cope with export flows. Based on interviews with the sector’s agents and on a comparative analysis of transportation costs, this paper aims to identify and evaluate infrastructure bottlenecks that affect the Brazilian frozen beef logistics chain and the economic gains that could be achieved by directing more frozen beef exports through the country’s Northern Arc ports. Among the results obtained from analyzes of frozen beef export flows from the state of Mato Grosso, the Brazilian state with the greatest number of plants that process beef for export, the use of Northern Arc ports can bring road transportation cost savings of up to 43% for some localities. It was also found that the lack of maritime shipping capacity, whether from restricted port capacity or infrequent ship departures, is one of the main logistical problems impeding the flow of frozen beef from ports inBrazil’s north.